EL GASTO PÚBLICO A NIVEL GLOBAL Y POR GRUPO DE PAÍSES Y SU INCIDENCIA EN EL CAPITAL HUMANO, PERÍODO 1970-2016" - Mora González, Elita Jhomayra (2019)
Public spending is one of the main determinants of human capital, since education and qualification as the main assets and so that can compete effectively and efficiently in the labor market. An increase in public spending on the aforementioned human capital tends to rise up the capacities of workers, to increase their individual contribution, which leads to an increase in total production, with the resulting economic growth. However, this public expenditure is not carried out by the countries in an optimal way, generating a minimum participation of human capital in the development processes. Therefore, the investigation was carried out; Public expenditure at the global level and by group of countries and its impact on human capital, period 1970-2016, whose general objective is; Determine the behavior of public spending, globally and by groups of countries, period 1970-2016, through a descriptive study, using cointegration techniques with panel data, with the purpose of establishing its effect on human capital. The database used to measure public expenditure of the 55 countries in the present investigation was obtained from the World Development Indicators (WDI, 2017), the World Bank (2017) and the total adult literacy rate (average years of schooling between 5 to 17 years) as a proxy of the human capital of the database of Barro and Lee (2013). The scientific method with its inductive, deductive, analytical, synthetic and statistical expressions. As a technique, the econometric was used with panel data. The results show that, through cointegration techniques with panel data, we find that there is cointegration of short-term equilibrium between the variables public expenditure and human capital, pointing out, on the one hand, that public spending has a positive effect on capital human in the short term and, on the other hand, that globally there is no long-term